Demand of sports and leisure for youth in the city of Novo Hamburgo, Brazil - GUSTAVO ROESE SANFELICE; ELENARA JAHN; THAÍS DALZOCHIO (Revista Latinoamericana en Ciencias Sociales, Niñez y Juventud)
...